Use of Knowledge Management Tools and Techniques in Academic Libraries in India: A Study - Sudarshan Rao, S. (Journal of Information and Knowledge, 2016)
Defines Knowledge Management (KM) and explains its importance in both corporate business organizations and also in not for profit service organizations, including libraries, as a means of improving performance and to develop quality products and services. States that KM tools play an important role, and institutions use more than one KM tool in general for effective KM implementation. The objective of the study is to find out the use of different KM tools and their preferences in academic institutions / libraries in India. The study used Survey Method. Random Sampling method is used to collect the data from a sample of 50 university libraries comprising of central, state, private and deemed universities in India through questionnaire technique. The major findings of the study are: only 34.0% of the university libraries in India are implementing KM in their libraries. Internet, Intranet, Help Desk Technologies and Document management Systems are the preferred KM tools in the decreasing order of importance in the academic institutions. 'Communication and Messaging' is observed to be the most important purpose of use of KM tools in the universities or university libraries in India.